Embryonic origin and compartmental organization of the external genitalia - Herrera, Ana M. (Sci Rep, 2014)
Genital malformations occur at a high frequency in humans, affecting ~1:250 live births. The molecular mechanisms of external genital development are beginning to be identified; however, the origin of cells that give rise to external genitalia is unknown. Here we use cell lineage analysis to show that the genital tubercle, the precursor of the penis and clitoris, arises from two populations of progenitor cells that originate at the lateral edges of the embryo, at the level of the posterior hindlimb buds and anterior tail. During body wall closure, the left and right external genital progenitor pools are brought together at the ventral midline, where they form the paired genital swellings that give rise to the genital tubercle. Unexpectedly, the left and right external genital progenitor pools form two lineage-restricted compartments in the phallus. Together with previous lineage studies of limb buds, our results indicate that, at the pelvic level, the early lateral mesoderm is regionalized from medial to lateral into dorsal limb, ventral limb, and external genital progenitor fields. These findings have implications for the evolutionary diversification of external genitalia and for the association between external genital defects and disruption of body wall closure, as seen in the epispadias-extrophy complex.